INVENTARISASI GASTROPODA DI LANTAI HUTAN MANGROVE DESA RAP-RAP KABUPATEN MINAHASA SELATAN SULAWESI UTARA - Rangan, Jety K (Sam Ratulangi University, 2010)
The mangrove forest is a transitional ecosystem between land and sea. As a transition area between land and sea, mangrove forest ecosystems have environmental properties of a sharp gradient. Tides can result in changes in several environmental factors, mainly temperature and salinity. One type of animal that can tolerate these environmental changes are of a group of mollusks. The purpose of this study was to identify the types of mollusks (Gastropoda) found on the floor of Mangrove Forest, using transects squares drawn perpendicular from the shoreline mangrove cutting edge. From this research activity gastropods found in the floor of mangrove forest-Rap Rap village consists of five phyla, and nine species, namely: Family Cerithiidae, namely Cerithium cobelty and Clypeomorus coralium. Family Littorinidae are Littoraria scabra, family Muricidae are Chicoreus capucinus, and morula margariticola Drupella rugosa, from the family of Nassarius Nassariidae Potamididae margaritifer and family, namely Telescopium telescopium and Terebralia sulcata.